On decompositions of the systems of roots of Кас-Moody algebras of rank 2 - Tutov , A. A.; Futorny , V. M. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
A classifications is presented of the parabolic decompositions of the system of roots of Kac—Moody algebras of rank 2. New series of irreducible representations are constructed.